Bloqueio contínuo do nervo ciático. - Maria Lurdes Castro; Teresa Rocha (Acta Médica Portuguesa, 2008)
Although perioperative pain is multifactorial, there are two main factors on which we can act upon: the central sensitization - using opioid analgesics - and the peripheral nociceptive stimulus - by means of a peripheral nerve block. The use of these techniques for anesthesia and post-operative analgesia is increasingly frequent in orthopaedic surgery because they provide excellent sensitive and motor block and offer advantages over other types of analgesia concerning pain relief and early mobilization in the post-operative period. We present a clinical case in which we made a continuous sciatic block (popliteal approach) in a fourteen years old girl with a Hyperactivivity Syndrome and Mental Re-tardation proposed for a club foot corrective surgery, allowing an effective perioperative analgesia with minimum side effects and a quick return to her familiar environment.